Implementation of Da’wah in Counteracting Hoax News on Social Media - Husniya, Eta Amala; Auliya, Mikhlathul; Nafisah, Iklil (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2023)
The primary objective of this study is to examine the significance of da'wah values within the MAFINDO (Masyarakat Anti Fitnah Indonesia) website as a means to combat hoax news on social media. The research methodology employed is content analysis, which helps reveal the contents of the research instrument. The study utilizes the Media Dependency Theory to evaluate MAFINDO's image as portrayed in several of its posts. In this particular case, the Media Dependency Theory serves as a tool to better understand how da'wah values manifest in the content presented on the MAFINDO website, aiming to counter hoax news on social media. The study's findings indicate the presence of two da'wah values on the website. Firstly, the MAFINDO website serves as a platform for truth, promoting the value of information disclosure. Additionally, the value of da'wah is evident in the